The Impact of Transfer Pricing, Return on Assets, Leverage, Firm Size, and Tax Havens toward Income Shifting (An Empirical Study of Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2019–2022) - Bahiyyah, Siti Lu’lu’ul; Setiany, Erna (Dinasti Publisher, 2026)
The study was conducted with the aim of analyzing the influence of transfer pricing, return on assets, leverage, firm size, and tax haven on income shifting (an empirical study of energy sector companies listed on the Indonesia Stock Exchange from 2019-2022. The method used a quantitative method with an explanatory research type. The populations selected of the study are all Energy Companies listed on the IDX from 2019-2022 by totaling 75 Companies. The sampling technique of the study used a purposive sampling technique. The data analysis method used panel data with the Eviews software program version 10. The study found that transfer pricing has no effect on income shifting, return on assets has effect on income shifting, leverage has effect on income shifting, firm size has effect on income shifting, and tax haven has effect on income shifting in energy sector companies listed on the IDX for the period 2019-2022.